2015
DOI: 10.3324/haematol.2015.124131
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for ocular chronic graft-versus-host disease diagnosis and disease activity in transplant clinical practice

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nOcular cGvHD predictive models haematologica | 2015; 100(9) 1229 cGvHD manifestations, a diagnosis of ocular cGvHD can be made. This diagnostic scoring system has not yet been prospectively validated, and exact ophthalmology criteria for cGvHD diagnosis remain to be defined. The National Institutes of Health (NIH) cGvHD Consensus Project in 2005 proposed guidelines for transplant clinicians to assess ocular cGvHD severity; specified measures were the NIH eye score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Sixty two percent of HSCT patients developed oGVHD, consistent with a previous NIH-based study [26]. The incidence of oGVHD in the literature ranges from 12-55% [8,10,25,27].…”
Section: Discussionsupporting
confidence: 87%
“…Sixty two percent of HSCT patients developed oGVHD, consistent with a previous NIH-based study [26]. The incidence of oGVHD in the literature ranges from 12-55% [8,10,25,27].…”
Section: Discussionsupporting
confidence: 87%
“…the National Institutes of Health Eye Score and Schirmer's test, 19 and a multiple conjunctival gene-based predictive model. 12 Multiple biomarker-based models, built upon the simultaneous use of a group of biomarkers, may improve performance compared to the use of a single-molecule analysis for diagnosis issues.…”
Section: Figurementioning
confidence: 99%
“…Predictive models have also focused on clinical parameters in an effort to determine which aspects are most predictive of ocular cGVHD diagnosis. 19 Additionally, model validation is necessary as it gives important information about the reliability of the process. Thus, the purpose of this study was to develop and validate a prediction model for the diagnosis of ocular cGVHD based on the levels of a panel of inflammatory mediators in tears and the correlation of those mediators with the clinical ophthalmic phenotype.…”
mentioning
confidence: 99%
“…These scales are based on findings for the lid margin or meibomian glands, although their utility for ocular GVHD has not been well validated. One study showed the utility of the meibomian gland plugging score (0 = none; 1 = 1 to 2 glands; 2 = 2 to 3 glands; 3 = all 5 glands, lid margin swelling) for diagnosing ocular GVHD [37].…”
Section: Meibomian Scorementioning
confidence: 99%
“…All other moderately symptomatic situations are assigned a score of 2. The NIH eye score combined with the Schirmer test has shown >90% sensitivity and specificity for the diagnosis of ocular GVHD [37]. In the context of response assessment in clinical trials, the NIH eye score is recommended as a simple and reliable measure [48], whereas the Schirmer test is no longer recommended because of its poor correlation with changes in ocular GVHD symptoms [39].…”
Section: Diagnosis Staging and Response Criteriamentioning
confidence: 99%